Pengaruh Stimulasi Massage Terhadap Penurunan Kadar Bilirubin Pada Neonatus di RSUD Dr Moewardi Surakarta - Naufal, Adnan Faris, Agus Widodo, S.Fis, M.Kes, Edi Waspada. S.Fis, M Kes (2016)
Background: Bilirubin is one indicator of the health of the views of organs, especially the liver function in neonates. Increased bilirubin is physiologically occur in neonates aged 3-10 days with a concentration of no more than 10 mg / dl. In the event of an increase in bilirubin levels exceeding the physiological limits will result in bilirubin encephalopathy and even death. One of the stimulation can be used to reduce bilirubin levels is by stimulating massage Objective: Knowing the effect of massage stimulation to decreased levels of bilirubin in neonates. Methods: The research is a qualitative design with pre and post test one control group design, the sample of which is used only use one group was given stimulation massage treatment with duration of 15 minutes using the field. Measurement of the bilirubin level is done with the data retrieval laboratory results levels of total bilirubin. The data analysis was made in the form of data description, which is the form of the number of Total Bilirubin levels will be measured using laboratory results, are presented in graphical form which will be measured at the beginning and end of the study for each sample. Results: There is the effect of a decrease in bilirubin levels in neonates with conditions given Hiperbilirubin after stimulation massage Conclusion: There is the effect of a Decrease in bilirubin levels in neonates with hyperbilirubinemia given conditions after stimulation massage